Influence of weather parameters and insect pest populations on incidence and development of sheath rot of rice - and A.G.R. REDDY, M.M. REDDY, C.S. REDDY* (Indian Phytopathology, 2002)
Results of two years experimentation indicated that the sheath rot incidence of rice was more in kharif season than in rabi season. Correlation analysis has shown that relative humidity is having positive correlation with disease index, whereas temperature and sunshine are negatively correlated. Influence of maximum relative humidity is significant on all the 22 plantings while that of minimum was significant in few plantings only. Negative influence of minimum temperature was significant on all the 22 plantings whereas that of maximum temperature and sunshine hours was significant in some plantings only. Though disease development was observed at 50 per cent maximum RH it was rapid at above 80 per cent and slow between 60-80 per cent. Correlation analysis between disease index and insect pest populations showed no relationship between the populations of insects caught in light trap and development of disease in the field.